Initial Psychometric Assessment of a Multidimensional Concept Test Addressing Ethnomedicine, Phytochemistry, and DPPH–IC50 Antioxidant Assay Analysis - Faizul Bayani; Joni Rokhmat; Aliefman Hakim; AA Sukarso (Postgraduate Program, University of Mataram, 2026)
Multidisciplinary training involving ethnomedicine and ethics, phytochemistry, and antioxidant bioassay analysis requires students to integrate normative reasoning, chemical concepts, and quantitative data analysis. Therefore, foundational competency and assessment quality must be established before diagnostic application. This study evaluated the first psychometric effectiveness of a multidomain idea test and outlined pre-intervention baseline performance across the three domains. The examination was administered to fifth-semester undergraduate pharmacy students enrolled in the Phytochemistry course at the Faculty of Health and Science, UNIQHBA Bagu. A 28-item mixed-format assessment, comprising multiple-choice, constructed-response, and numerical items (maximum score of 32), was administered to N = 41 pupils. Subsequently, descriptive statistics and indices from Classical Test Theory were computed, including Cronbach's alpha, item difficulty (p), D27 discrimination, and adjusted item-total correlations. The most challenging and simplest collections of objects were employed to encapsulate the extreme items. The average total score was 19.90 out of 32 (62.20% ± 13.05%), the median was 20, the range was 11 to 29, and 9 students (about 22.0%) achieved the ≥70 criterion. The performance in the domain was inconsistent. Ethnomedicine and ethics achieved a score of 7.88 ± 1.25 (78.80% of the maximum), phytochemistry received 7.29 ± 2.15 (72.90%), and DPPH–IC50 interpretation got 4.73 ± 2.54 (39.40%). The reliability was acceptable (alpha = 0.756), but the item diagnostics revealed floor and ceiling effects, along with DPPH–IC50 items that were notably challenging. The technique is suitable for initial diagnostic profiling and highlights DPPH–IC50 quantitative interpretation as the main baseline gap, thereby promoting targeted scaffolding and item adjustment to improve differentiation across the ability spectrum